The De-Stalinization in the Communist Youth of Chile and the Construction of an Alternative Youth Culture (1956-1964) [la Desestalinización en Las Juventudes Comunistas de Chile y la Construcción de Una Cultura Juvenil Alternativa (1956-1964)] - Alvarez-Vallejos, R (Universidad de Chile, Facultad de Filosofia y Humanidades, Departamento de Literatura, 2020)
This article examines the repercussions of the process of de- Stalinization in the Communist Party of Chile and its youth wing. Initiated in 1956 by Nikita Khrushchev s "Secret Speech" to the 20th Congress of the Communist Party of the Soviet Union, de-Stalinization has been understood by some scholars of European Communism as signaling the terminal crisis of International Communist Movement. By focusing on Chile, this article broadens the discussion on the international repercussions of de-Stalinization to include Latin America, whose social and political realities differed from that of Europe. It argues that de- Stalinization put forth a new and improved version of Communism, which helped the Communist Youth of Chile recruit new members. Influences coming from the Soviet Union during the process de-Stalinization were crucial in the development -on the part of Chilean Communists- of an alternative youth culture, which began to take root in Chile in the 1960s. © 2020 Universidad de Chile, Facultad de Filosofia y Humanidades, Departamento de Literatura. All rights reserved.